Evidence for Divergence of the Genus ‘Solwaraspora’ Within the Bacterial Family Micromonosporaceae - Hailee I. Porter; Imraan Alas; Nyssa K. Krull; Doug R. Braun; Scott R. Rajski; Brian T. Murphy; Tim S. Bugni (Microorganisms, 2025)
The purpose of this study was to investigate the taxonomic and phylogenomic placement of the proposed genus ‘Solwaraspora’ within the context of other marine genera using a dual-omics approach. Initially, we isolated bacteria from marine tunicates, squirts, and sponges, which were morphologically similar to an emerging genus (identified as ‘Micromonospora_E’ by the GTDB-tk2 database using whole genome sequence data) by colony shape, size, and clustering pattern, but only found five strains in our dataset belonging to this distinction. Due to the minimally explored nature of this genus, we sought to identify more bacterial strains with similar morphology to Micromonospora‘Micromonospora_E’ by whole genome sequencing (WGS). Within our collection, we noted 35 strains that met this criterion and extracted genomic information to perform WGS on these strains. With this information, we studied taxonomic and phylogenomic relationships among these organisms. Using the data gathered from WGS, we were able to identify an additional five strains labeled by the GTDB-tk2 database as Micromonospora‘Micromonospora_E’, as well as construct phylogenomic trees to examine the evolutionary relationships between these strains. ANI values were calculated between strains from our dataset and type strains of Micromonospora and Plantactinospora as well as against an outgroup Streptomyces strain. No type strains are available for ‘Solwaraspora’. Using MALDI-TOF MS, we positively identified ‘Solwaraspora’, which was supported by the phylogenomic tree showing Micromonospora’Micromonospora_E’ (‘Solwaraspora’) in a distinct clade from Plantactinospora and Micromonospora. Additionally, we discovered gene cluster families (GCFs) in alignment with genera, as well as a large representation of biosynthetic gene clusters (BGCs) coming from the ‘Solwaraspora’ strains. These findings suggest significant potential to discover novel chemistry from ‘Solwaraspora’, adding to the importance of investigating this new genus of bacteria.